STUDENTS’ PERCEPTIONS IN IMPLEMENTING CLASSROOM DEBATING STRATEGY TO INCREASE STUDENTS’ SPEAKING SKILL - Yucha Dwistya; Aswadi Jaya; Hermansyah (Esteem Journal of English Education Study Programme, 2024)
This study aimed to investigate university students' perspectives regarding the implementation of classroom debating strategies to enhance speaking skills. This study employed a descriptive qualitative methodology involving the distribution of questionnaires, conducting interviews, and gathering documentation. To assess the data, the researcher employed a 5-point Likert scale, which contained twenty items in the questionnaire and five questions during the interview session. Thirty-six respondents completed a full questionnaire, while eight students participated in an interview session with detailed questions. The findings of this study indicate that university students possess favorable attitudes regarding the utilization of classroom debate strategies to enhance their speaking skills. The debate effectively motivated students to enhance their speaking skills and improve several elements of speaking, including vocabulary, pronunciation, fluency, comprehension, and grammar. University students encounter numerous hurdles in executing classroom debating strategies, including difficulties in defining the motion, articulating reasons, formulating rebuttals to opponents' arguments, structuring logical and coherent discourse, and managing uneasiness and anxiety during presentations.